ESTUDIOS SOBRE LA RESERVA PROTEICAII EFECTOS DE LA INYECCION PARENTERAL DE LIQUIDOS OCULARES SOBRE LA INTOXICACION TIROIDEA EN LA RATA BLANCA - TAPIA, MARCO A; SOTO VERGARA, EDUARDO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
Rats injected with ocular fluids from ox eyes were found less sensitive (lower mortality, lesser loss of wt) to toxic doses of thyroid prepns than control animals As it is well known that myxedematous patients are also more tolerant to thyroid prepns,
CIENC MEX
Keywords: ESTUDIOS, RESERVA, PROTEICAII, INYECCION, PARENTERAL, LIQUIDOS, OCULARES, INTOXICACION, TIROIDEA; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA VETERINARIA